Neuroprotective Effects of Probiotic-Supplemented Diet on Cognitive Behavior of 3xTg-AD Mice. (5th January 2022) - Tan, Chenxi; Liu, Yang; Zhang, Huiyi; Di, Cihan; Xu, Dechao; Liang, Chunming; Zhang, Ningning; Han, Bing; Lang, Weiya
Abstract : Alzheimer's disease (AD) is recognized as one of the most common types of senile dementia. AD patients first suffer memory loss for recent events (short-term memory impairment). As the disease progresses, they are deprived of self-awareness. This study aims to explore the effects of a probiotic-supplemented diet on the cognitive behaviors and pathological features of mouse models of Alzheimer's disease (AD). Mice in the control group and the 3xTg-AD group were fed a regular diet and a probiotic-supplemented diet, respectively, for 20 weeks. Behavioral experiments like Morris's water maze and Y maze were conducted. Then, feces of mice were collected for 16S sRNA gene sequencing for microorganisms. In the end, soluble and insoluble A β 40 and A β 42 in the hippocampus and cortex of mice in each group were quantitatively analyzed with a double-antibody Sandwich ELISA. The expression levels of tau protein and gliocyte in the hippocampus and cortex were detected using the Western Blot method. The result of the Morris water maze experiment indicated that, in the place navigation test, the mice in the 3xTg-AD group experienced a significant decline in the learning ability and a longer escape latency and in the space exploration test, the swimming time of mice in the 3xTg-AD group in the target quadrant decreased and after being treated with the probiotic diet, mice in the 3xTg-AD group had improved learning and memory ability. The result of Y maze showed that the probiotic diet can improve the spontaneous alternation accuracy of mice in the 3xTg-AD group. The result of 16s rRNA gene sequencing showed that, compared with mice in the WT group, those in the 3xTg-AD group experienced a change in the intestinal flora. The Western Blot result displayed a decreased expression level of tau (pS202) (P < 0.05 ) and decreased expression levels of Iba-1 and GFAP (P < 0.05 ). The result of the ELISA experiment showed decreased levels of soluble and insoluble A β 40 and A β 42 in 3xTg-AD mice (P < 0.05 ). In conclusion, a probiotic diet can prevent and treat AD by improving the intestinal flora of 3xTg-AD.